The relationship between entrepreneurial orientation, human resource management practices, organizational innovation and managerial ties to SME performance - Nazlina, Zakaria (2016)
Malaysian small and medium enterprises (SMEs) still have not performed to their fullest potential. SMEs have to focus on factors required to improve their performance. Therefore, this study is undertaken to investigate the possible variables that could better explain the performance of SMEs by investigating the relationship between entrepreneurial orientation (EO), human resource management (HRM) practices (i.e. communication and information sharing, compensation, job design, performance appraisal, selection, training and development) and organizational innovation on organizational performance. Specifically, it aims to investigate both the mediating roles of organizational innovation on the relationship between EO and HRM practices towards organizational performance and the moderating role of managerial ties on the relationship between organizational innovation and organizational performance. Resource-based view theory and social capital theory are integrated to explain the possible relationship between the variables in the research model. A total of 321 owners/managers of manufacturing SMEs, representing a response rate of 60.5%, participated in this study. Data was collected via self-administered questionnaires. PLS-SEM was used to analyze the data and test the hypotheses. Statistical results show that EO and certain HRM practices (i.e. communication and information sharing, compensation, performance appraisal, selection, training and development) are positively related to organizational innovation. Organizational innovation is also found to be positively related to organizational performance. Moreover, results reveal that organizational innovation mediates the relationship between EO and certain HRM practices (i.e. communication and information sharing, compensation, performance appraisal, selection, training and development) and organizational performance. However, no empirical support is found for the moderating effect of managerial ties on the relationship between organizational innovation and organizational performance. Finally, theoretical and methodological contributions, managerial implications and recommendations for future research are discussed.